2019
DOI: 10.1126/sciadv.aax2705
|View full text |Cite
|
Sign up to set email alerts
|

ATAT1-enriched vesicles promote microtubule acetylation via axonal transport

Abstract: The axonal transport of vesicles promotes microtubule acetylation across species.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Whether SETD2 methylates α−tubulin prior to or after assembly of α/β tubulin dimers into microtubules is not known. However, Even et al, reported that ATAT-1 is transported by vesicles along the length of microtubules, accessing K40 to acetylate this residue via pores in the microtubule shaft 15 . These and other studies have led to the growing appreciation that lattice dynamics of even stable microtubules can provide access to luminal residues along the shaft of microtubule polymers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether SETD2 methylates α−tubulin prior to or after assembly of α/β tubulin dimers into microtubules is not known. However, Even et al, reported that ATAT-1 is transported by vesicles along the length of microtubules, accessing K40 to acetylate this residue via pores in the microtubule shaft 15 . These and other studies have led to the growing appreciation that lattice dynamics of even stable microtubules can provide access to luminal residues along the shaft of microtubule polymers.…”
Section: Discussionmentioning
confidence: 99%
“…The pellet was removed and supernatants collected as whole cell extract for immunoblotting and immunoprecipitation analysis for soluble proteins. For subcellular fractionation, the pellet was collected after centrifugation as above, and resuspended in a hypotonic buffer (10 mM HEPES, pH 7.2, 10 mM KCl, 1.5 mM MgCl2, 0.1 mM EGTA, 20 mM NaF, and 100 μM Na3VO4), and disrupted using a manual homogenizer for [15][16][17][18][19][20] times. Disruption of the cells was confirmed using a hemacytometer.…”
Section: Whole Cell Lysis and Sub-cellular Fractionationmentioning
confidence: 99%
“…Among these, BCL9L was the most highly enriched and most regulated interactor ( Fig. 4C-E); RNF20 forms a complex with RNF40 and participates in mitotic spindle assembly by monoubiquitinating the microtubule motor protein EG5 [28]; IFITM3 shares the same membrane topology and CD225/IFITM domain with TRARG1 [29,30]; ATAT1 and SPECC1L are involved in microtubule stabilization [31,32]; STEAP3 is a NADPH oxidoreductase involved in transferrin-dependent iron uptake [33,34]. Genes were knocked down by siRNA and GLUT4 translocation to the PM was measured in adipocytes expressing a GLUT4 reporter construct with an HA-tag in the first exofacial loop and mRuby3 at the cytosolic C-terminal tail (HA-GLUT4-mRuby3).…”
Section: Functional Screening Of Selected Trarg1 Interactorsmentioning
confidence: 99%
“…This ex vivo protocol has been developed to investigate axonal transport in a physiological setting closely reproducing the in vivo environment. For complete details on the use and execution of this protocol, please refer to Even et al. (2019) .…”
mentioning
confidence: 99%
“…For complete details on the use and execution of this protocol, please refer to Even et al. (2019) .…”
mentioning
confidence: 99%